Lung recruitment by continuous negative extra-thoracic pressure support following one-lung ventilation: an experimental study - Schranc, Álmos; Diaper, John; Südy, Roberta; Peták, Ferenc; Habre, Walid; Albu, Gergely (Frontiers in Physiology, 2023)
Lung recruitment maneuvers following one-lung ventilation (OLV) increase the risk for the development of acute lung injury. The application of continuous negative extrathoracic pressure (CNEP) is gaining interest both in intubated and non-intubated patients. However, there is still a lack of knowledge on the ability of CNEP support to recruit whole lung atelectasis following OLV. We investigated the effects of CNEP following OLV on lung expansion, gas exchange, and hemodynamics. Ten pigs were anesthetized and mechanically ventilated with pressure-regulated volume control mode (PRVC; FiO2: 0.5, Fr: 30–35/min, VT: 7 mL/kg, PEEP: 5 cmH2O) for 1 hour, then baseline (BL) data for gas exchange (arterial partial pressure of oxygen, PaO2; and carbon dioxide, PaCO2), ventilation and hemodynamical parameters and lung aeration by electrical impedance tomography were recorded. Subsequently, an endobronchial blocker was inserted, and OLV was applied with a reduced VT of 5 mL/kg. Following a new set of measurements after 1 h of OLV, two-lung ventilation was re-established, combining PRVC (VT: 7 mL/kg) and CNEP (−15 cmH2O) without any hyperinflation maneuver and data collection was then repeated at 5 min and 1 h. Compared to OLV, significant increases in PaO2 (154.1 ± 13.3 vs. 173.8 ± 22.1) and decreases in PaCO2 (52.6 ± 11.7 vs. 40.3 ± 4.5 mmHg, p < 0.05 for both) were observed 5 minutes following initiation of CNEP, and these benefits in gas exchange remained after an hour of CNEP. Gradual improvements in lung aeration in the non-collapsed lung were also detected by electrical impedance tomography (p < 0.05) after 5 and 60 min of CNEP. Hemodynamics and ventilation parameters remained stable under CNEP. Application of CNEP in the presence of whole lung atelectasis proved to be efficient in improving gas exchange via recruiting the lung without excessive airway pressures. These benefits of combined CNEP and positive pressure ventilation may have particular value in relieving atelectasis in the postoperative period of surgical procedures requiring OLV.